Deskripsi Dasar Pemberitaan Injil dalam Roma 1:1-5 - Chandra, Adi; Angkouw, Semuel Ruddy; Dwikoryanto, Matius I Totok (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
Every human being who has been saved must be willing to devote himself and be dedicated to evangelism for people who do not know salvation in Jesus. The existence of a wrong paradigm on the basis of the content of the news then the message conveyed is not right and can also deviate from the essence of the news. Through descriptive qualitative method with a literature study approach, it can be concluded that the basic description of the preaching of the gospel in Romans 1:1-5 is an understanding that can bring perspectives in carrying out missions. Because the basis of the gospel can provide enthusiasm in spreading the gospel message. The results of the analysis found that the basis of the preaching of the gospel from the Book of Romans 1: 1 -5 is the first, the gospel is the gospel of God, this is the gospel that comes from the heart and the initiative of God to save people. Second, the Gospel is God's promise that was confirmed in the person of Jesus as the messiah or savior of sinners. Third, the Gospel Is About Jesus, this is based on the core and important purpose of the Gospel is the person of Jesus Christ who is God. The fourth is that the gospel is the message to lead people to eternal salvation.AbstrakSetiap pribadi manusia yang sudah diselamatkan harus mau mengabdikan diri dan berdedikasi melakukan penginjilan bagi orang yang belum mengenal keselamatan dalam Yesus.  Adanya paradigma yang salah terhadap dasar dari isi berita maka pesan yang disampaikan tidak tepat dan bisa juga menyimpang dari esensi berita tersebut. Melalui metode kualitatif deskritif dengan pendekatan studi literature maka dapat disimpulkan bahwa deskripsi dasar pemberitaan Injil dalam Roma 1:1-5 adalah pemahaman yang dapat membawa cara pandang dalam melakukan misi. Sebab dasar dari Injil tersebut dapat memberikan  semangat dalam mengabarkan berita Injil. Hasil dari analisis ditemukan bahwa dasar dari pemberitaan injil dari Kitab Roma 1 : 1 -5 adalah yang pertama, Injil adalah Injil Allah ini merupakan Injil yang berasal dari Hati dan Inisiatif Allah untuk menyelamatkan manusia. Yang kedua, Injil Adalah Janji Allah yang ditegaskan pada pribadi Yesus sebagai mesias atau penyelamat manusia berdosa. Ketiga,  Injil Adalah Tentang Yesus, ini mendasarkan bahwa inti dan tujuan penting dari Injil adalah pribadi Yesus Kristus yang adalah Tuhan. Yang keempat adalah Injil merupakan Berita untuk menuntun orang pada keselamatan kekal.